High‐density lipoprotein 3 and apolipoprotein A‐I alleviate platelet storage lesion and release of platelet extracellular vesicles. Issue 9 (10th June 2014) - Pienimaeki‐Roemer, Annika; Fischer, Astrid; Tafelmeier, Maria; Orsó, Evelyn; Konovalova, Tatiana; Böttcher, Alfred; Liebisch, Gerhard; Reidel, Armin; Schmitz, Gerd
<x xml:space="preserve">Abstract</x> Background Stored platelet (PLT) concentrates (PLCs) for transfusion develop a PLT storage lesion (PSL), decreasing PLT viability and function with profound lipidomic changes and PLT extracellular vesicle (PL‐EV) release. High‐density lipoprotein 3 (HDL3) improves PLT homeostasis through silencing effects on PLT activation in vivo. This prompted us to investigate HDL3 and apolipoprotein A‐I (apoA‐I) as PSL‐antagonizing agents. Study Design and Methods Healthy donor PLCs were split into low‐volume standard PLC storage bags and incubated with native (n)HDL3 or apoA‐I from plasma ethanol fractionation (precipitate IV) for 5 days under standard blood banking conditions. Flow cytometry, Born aggregometry, and lipid mass spectrometry were carried out to analyze PL‐EV release, PLT aggregation, agonist‐induced PLT surface marker expression, and PLT and plasma lipid compositions. Results Compared to control, added nHDL3 and apoA‐I significantly reduced PL‐EV release by up to −62% during 5 days, correlating with the added apoA‐I concentration. At the lipid level, nHDL3 and apoA‐I antagonized PLT lipid loss (+12%) and decreased cholesteryl ester (CE)/free cholesterol (FC) ratios (−69%), whereas in plasma polyunsaturated/saturated CE ratios increased (+3%) and CE 16:0/20:4 ratios decreased (−5%). Administration of nHDL3 increased PLT bis(monoacylglycero)phosphate/phosphatidylglycerol (+102%) and phosphatidic acid/lysophosphatidic acid (+255%) ratios and improved thrombin receptor–activating peptide 6–induced PLT aggregation (+5%). Conclusion nHDL3 and apoA‐I improve PLT membrane homeostasis and intracellular lipid processing and increase CE efflux, antagonizing PSL‐related reduction in PLT viability and function and PL‐EV release. We suggest uptake and catabolism of nHDL3 into the PLT open canalicular system. As supplement in PLCs, nHDL3 or apoA‐I from Fraction IV of plasma ethanol fractionation have the potential to improve PLC quality to prolong storage.